HIERARKI PERATURAN PERUNDANG-UNDANGAN HUKUM EKONOMI SYARIAH DALAM PERBANKAN SYARIAH - Fatma, Ulafa; Komarudin, Koko (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Legal hierarchy is a term used for a legal structure that is tiered to become the basis for the authorities authorized to form it. Low norms are based on high norms, so that low (inferior) norms do not conflict with higher (superior) norms. The basis of the highest hierarchical sharia law is Islamic law, then other laws refine and are formed based on previous laws. This research uses a library research approach, with a qualitative descriptive method, looking for relevant sources related to the problem and then describing the data to describe the regulatory framework for Islamic economic law for use in sharia banking. This article will discuss the hierarchy of sharia economic law and regulations used in sharia banking. The two legal bases used in sharia banking are normative law (Islam) and positive law (state). Sharia financial institutions and the public can use this hierarchy as a reference in carrying out sharia contract transactions and resolving sharia economic law disputes.